Regional Resource Management Based on Landscape Ecology in Northern Muria Peninsula, Central Java - Joko Wiyono; Sunarto sunarto (Indonesian Journal of Geography, 2016)
Landscape ecology can be used to identify potential resources based on it physical, biological and socio-cultural characteristics. This research was conducted in the northern part of the Muria Peninsula. This study uses observation and sampling based on toposequences transects. The northern Muria Peninsula is a complex area. Landscape in this region is strongly influenced by volcanism in the past of Muria Volcano and Genuk Volcano also geomorphological processes such as fluvial and marine. Potential resources in the northern part of the Muria Peninsula such as potential for marine, mining, agriculture, farming, and tourism. Muria Peninsula regional management should be adapted to the potential and function of each area, so that will not cause environmental degradation.